One-pot conversion of levulinic acid into gamma-valerolactone over a stable Ru tungstosphosphoric acid catalyst. (1st April 2021) - Koley, Paramita; Rao, B. Srinivasa; Shit, Subhash Chandra; Sabri, Ylias; Mondal, John; Tardio, James; Lingaiah, N.
Graphical abstract: Highlights: Selectivity towards gamma-valerolactone (GVL) highly dependent on extent of Brønsted acidity. Very high specific reaction rate at moderate temperature compared to previously reported Ru based catalysts. Developed catalyst showed only minor reduction in activity after five cycles of testing using simple regeneration process. Abstract: In this paper ruthenium exchanged tungstophosphoric acid (TPA) catalysts with different ruthenium loading (Rux TPA (x = 1, 2, 3)) were studied for conversion of levulinic acid (LA) into gamma-valerolactone (GVL) (a potential fuel/fuel additive). Studies were also conducted on a Ru/C catalyst as Ru/C catalysts have recently been reported to have significant promise for this reaction. Under the conditions used (130 °C, 1.0 MPa H2, 2 h in 1, 4 dioxane solvent) one of the prepared catalysts achieved excellent conversion and selectivity to GVL. This catalyst also compared favorably to Ru/C catalysts that have been previously studied in terms of rate of production of GVL per gram Ru. Characterization studies showed that Ru metal surface area and extent of Lewis and Brønsted acidity were characteristics that had a significant influence on the conversion and selectivity of the Rux TPA catalysts studied. The best performing Ru3 TPA catalyst was found to be highly recyclable with only a slight decrease in selectivity of GVL (from 100% to 98.3%) being observed after five cycles of testing.